The Dynamics of The Wasathiyah Curriculum on The Content of Moderatism Education In The Subject of Akidah Akhlak MAS Tarbiyah Islamiyah - Ependi, Rustam; Tumiran, Tumiran; Lubis, Sakban (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Religious education is one of the important issues because the religious education provided in schools does not bring good multicultural education to life, and even tends to be the opposite. As a result, social conflicts are often hardened by the religious legitimacy taught in religious education in schools in conflict-prone areas. This makes conflicts that have roots in fundamental religious beliefs so that social conflict and violence are increasingly difficult to overcome, because it is understood as a religious calling. The roots of various social conflicts that result in prolonged anarchy are often problems that have nothing to do with religion, but in reality religion has always been an inseparable part of various social conflicts. The potential for conflict and disintegration is because religion in its manifestation is ambivalent towards unity and integrity, meaning that although religion has the power to unite it also has the power to divide.